Peragaan Perangkat Optik Untuk Pengukuran Teknik di SMK (Sekolah Menengah Kejuruan) Sasmita Jaya 2, Pamulang Barat, Tangerang Selatan - Ihat Solihat; Ersam Mahendrawan; Edi Tri Astuti (Jurnal Pengabdian Kepada Masyarakat Kalam, 2026)
This community engagement program was designed to improve vocational students’ conceptual understanding and practical skills in technical measurement through hands-on demonstrations of optical instruments in a school laboratory environment. The activities aimed to bridge the gap between abstract physics concepts and their application in technical practice, particularly in relation to measurement accuracy, instrument handling, and observational skills. An experiential learning approach was implemented, integrating interactive demonstrations, guided practice, and reflective discussion to promote active participation and meaningful learning. Student learning outcomes were assessed through formative evaluation and direct observation of engagement, comprehension, and procedural competence during the sessions. The findings indicate notable improvements in students’ understanding of optical principles, appropriate application of measurement techniques, learning motivation, and confidence in using laboratory equipment, highlighting the value of contextualized laboratory-based learning in vocational education.